PERTUMBUHAN EKONOMI: Analisis Fundamental Keuangan Daerah (Efisiensi, Efektivitas, & Modal) - Sahroni, Sahroni; Sutoro, Moh. (Sekolah Menengah Kejuruan (SMK) Pustek, 2021)
Economic growth is one indicator of a region's progress. Therefore, the local government seeks to increase it through many factors, one of which is maximizing the use of the budget. It is hoped that regional development can be realized in accordance with strategic plans, is right on target, and has an impact on the progress of community economic activities. This study aims to examine what factors influence economic growth in the city of South Tangerang. In practice, this research uses a quantitative approach. Regression analysis is used to explain the data. The research data were obtained through purposive sampling techniques. The results showed that economic growth in South Tangerang City will increase significantly if the efficiency factor increases. This means that economic development will be better if the use of the budget is right on target and according to the regional priority scale. Thus, the community can take advantage of the facilities that have been built by the local government to support economic activities.